2010
DOI: 10.1016/j.ecl.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Metabolism

Abstract: Synopsis The biologically active metabolite of vitamin D, 1,25(OH)2D3, affects mineral homeostasis and has numerous other diverse physiological functions including effects on growth of cancer cells and protection against certain immune disorders. This chapter reviews the role of vitamin D hydroxylases in providing a tightly regulated supply of 1,25(OH)2D3. The role of extrarenal 1α(OH)ase in placenta and macrophages is also discussed as well as regulation of the hydroxylases and vitamin D hydroxylases in aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
289
0
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 382 publications
(323 citation statements)
references
References 71 publications
3
289
0
18
Order By: Relevance
“…Other down‐regulating factors that are present in CKD patients include low availability of 25(OH)D, hyperphosphatemia, metabolic acidosis, and uraemia itself. Additionally, elevated FGF23 activates the enzyme 24‐hydroxylase (CYP24), hydroxylating both 25(OH)D and 1,25(OH) 2 D. 24‐hydroxylase limits the amount of 1,25(OH) 2 D in target tissues both by producing 24,25(OH) 2 D (thus decreasing the availability of 25(OH)D for 1 hydroxylation) or by accelerating the catabolism of 1,25(OH) 2 D to 1,24,25(OH) 3 D resulting in calcitroic acid, which is biologically inactive 76, 77. CKD is also considered as a state of vitamin D resistance, because VDR expression in bone cells and in nodular parathyroid glands is reduced 78.…”
Section: Vitamin D Metabolism In Chronic Kidney Diseasementioning
confidence: 99%
“…Other down‐regulating factors that are present in CKD patients include low availability of 25(OH)D, hyperphosphatemia, metabolic acidosis, and uraemia itself. Additionally, elevated FGF23 activates the enzyme 24‐hydroxylase (CYP24), hydroxylating both 25(OH)D and 1,25(OH) 2 D. 24‐hydroxylase limits the amount of 1,25(OH) 2 D in target tissues both by producing 24,25(OH) 2 D (thus decreasing the availability of 25(OH)D for 1 hydroxylation) or by accelerating the catabolism of 1,25(OH) 2 D to 1,24,25(OH) 3 D resulting in calcitroic acid, which is biologically inactive 76, 77. CKD is also considered as a state of vitamin D resistance, because VDR expression in bone cells and in nodular parathyroid glands is reduced 78.…”
Section: Vitamin D Metabolism In Chronic Kidney Diseasementioning
confidence: 99%
“…ous studies have shown that VDR-induced transcription is mediated by 1,25(OH) 2 D 3 -dependent recruitment of coregulatory complexes, which include p160 coactivators with histone acetyltransferase activity (1)(2)(3)(4). For chromatin remodeling to occur, the effects of acetylation are complemented by structural modifications that are ATP-dependent (19).…”
Section: Brg1-containing Swi/snf Complex Vdr and C/ebp␤ Cooperate Imentioning
confidence: 99%
“…1,25-Dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), 2 the hormonally active form of vitamin D, is produced by two sequential hydroxylations of vitamin D at C-25 in the liver by 25-hydroxylase and at C-1 by the enzyme 1␣-hydroxylase (3). 1,25(OH) 2 D 3 mediates its effects by binding to the vitamin D receptor (VDR), a member of the nuclear receptor family of transcription factors, which heterodimerizes with the retinoid X receptor and interacts with specific DNA sequences (vitamin D response elements) in target genes, resulting in activation or repression of transcription (1,2,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 1a-hydroxylase enzyme is abundant in variable non renal tissues so locally synthesized active form presents in most of human organs as it is under autonomous autocrine control [10]. Recently it was reported that 1a-hydroxylase enzyme can activate 25 (OH) vitamin D to active form in the central nervous system [11]. ASD are wide verity of developmental disorders of CNS characterized by disturbed social interaction, impaired speech and stereotypic movements [12].…”
Section: -Hydroxy Vitamin D (25 Ohmentioning
confidence: 99%